The Impact of Short - term Treatment on Torture Survivors. The Change in PTSD, Other Psychological Symptoms and Coping Mechanisms after Tretament - Arcel, Libby Tata (Array, 2003)
This chapter analyses the emotional and bodily reality of war-torture survivors on the basis of nine case-studies. Furthermore results on a quantitative analysis on treatment are presented. An intensive short-term comprehensive treatment of torture survivors over 3 months in a post-conflict society has positive results on almost all psychological symptoms (10-20 sessions divided among different professionals). A treatment of 6 months duration (20-30 sessions divided among different professionals) has better results on all kinds of psychological symptoms and PTSD except for Depression. Thus treatment must at least last 6 months, preferably longer, and until there is significant recovery in all areas of the survivors' life. The multidisciplinary treatment model has be shown to reduce the survivors health and mental health symptoms and increase his well-being. Furthermore, 3 months' treatment has shown to bring changes in coping mechanisms from mainly maladaptive to the direction of adaptive ones. People change their coping according to demands and opportunities from the environment. Subjective self-evaluation of improvement of well-being shows correlation to objective measured improvement.